Development of selective attention through play in higher education students. - Carpio Lozada , Blanca (Escuela Profesional de Ciencias de la Comunicación Social de la Universidad Nacional del Altiplano, 2020)
The research is focused on the application of the "DIMAPA" Games, which are a set of dynamic, entertaining, motivating and guided activities, based on drawings, mandalas and words designed for the General and Applied Histology and Embryology course; being the main objective of the work to develop the selective attention of the students of Dentistry. This is an applied type investigation, with an explanatory level, an experimental study with a quasi-experimental design and a quantitative approach. The sample of the experimental group consisted of 13 students and the control by 11, on which the attention test d2 was applied; after which the “DIMAPA” games were applied to the experimental group in 30 learning sessions, distributed over 4 per week. After the intervention, the d2 attention test was applied again to our two formed groups and the data obtained was processed. In the analysis and interpretation of the results, it was shown that, according to the Student's t test, the students to whom the "DIMAPA", games were applied significantly increased the development of their selective attention, according to the three parameters evaluated (effectiveness total: p = 0.034, concentration: p = 0.023 and variation: p = 0.048), therefore we conclude that the games "DIMAPA" develop selective attention; For this reason, the proposed alternative hypothesis is accepted rejecting the null (p <0.05).